Začasne odredbe v pravu industrijske lastnine - Remškar, Sara (Podjetje in delo, 2014)
Interim injunctions are an important remedy in a court of law, used to regulate a dispute between opposing parties until the case has been decided and even after. In industrial property legal cases they are even more important, especially because of the nature of this rights (most of them are namely time limited), which require prompt and effective protection. Through case law, I examine, whether such effective protection in Slovenian domestic law even exists. First, there is a brief presentation of industrial property rights, their significant importance for the economy, and legal protection. In the second part of the article, regulation of interim injunctions through domestic case law is presented.
Keywords: industrijska lastnina; reševanje; sodna praksa; spori